A comparative analysis of transitions generated using the Unity game development platform - Marek Tabiszewski (Journal of Computer Sciences Institute)
This paper conducts a comparative analysis of transitions generated using the Unity engine. It selects fifteen animations featuring a humanoid character, introduces breaks in marker trajectories, and fills them with transitions generated by the game engine's animator. These transitions are then compared with the unmodified original character animation. The study compares animations by calculating the average deviation in bone rotation and position between the original and generated motion throughout the animation. The results show that the Unity engine excels in generating transitions for slow animations involving the lower body limbs, with the largest errors occurring in the bones at the extremities of the limbs.